2017
DOI: 10.1002/biot.201600693
|View full text |Cite
|
Sign up to set email alerts
|

The fabrication of iron oxide nanoparticle‐nanofiber composites by electrospinning and their applications in tissue engineering

Abstract: This paper reviews the use of iron oxide nanoparticle-nanofiber composites in tissue engineering with a focus on the electrospinning technique. Electrospinning is an established method of scaffold fabrication offering a number of key advantages which include its facile nature, with electrospun materials offering a high surface area to volume ratio, potential for the release of drugs and antimicrobials, controllable fiber diameters and high porosity and permeability. A number of different techniques for the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 80 publications
(102 reference statements)
0
29
0
Order By: Relevance
“…Several different methods exist to produce scaffolds for tissue engineering. Most common are jetting methodologies such as aerodynamically assisted jetting/ threading, pressure‐assisted/driven jetting/spinning, laser‐guided writing, inkjet printing, electrospray, and electrospinning . Printing, electrospray, and electrospinning are currently undergoing a widespread revival of scientific investigation of chemical, physical, and biological outputs, being able to produce structures more similar in size to the natural extracellular matrix …”
Section: Representative Biomedical Applicationsmentioning
confidence: 99%
“…Several different methods exist to produce scaffolds for tissue engineering. Most common are jetting methodologies such as aerodynamically assisted jetting/ threading, pressure‐assisted/driven jetting/spinning, laser‐guided writing, inkjet printing, electrospray, and electrospinning . Printing, electrospray, and electrospinning are currently undergoing a widespread revival of scientific investigation of chemical, physical, and biological outputs, being able to produce structures more similar in size to the natural extracellular matrix …”
Section: Representative Biomedical Applicationsmentioning
confidence: 99%
“…It showed that the combined action of magnetic nanoparticles and the magnetic field can promote bone repair (Tang et al, 2017;Yang et al, 2018). Magnetic nanoparticles have been proven to promote bone tissue regeneration mainly through the magnetic force generated by itself and the external magnetic field (Mortimer and Wright, 2017;Lin et al, 2018b;Fernandes et al, 2019). Fernandes et al studied the effect of an FIGURE 4 | The schematic representation of the fabrication of a three-dimensional scaffold using a magnetoacoustics' field, including the assembly and recrystallization of the scaffold.…”
Section: Effect Of Magnetic Particles On Bone Repairmentioning
confidence: 99%
“…Electrospun nanofibrous membranes containing an amount of magnetic iron oxide nanoparticles have become a necessary material for various uses, including tissue engineering, sensors, wound dressings, magnetic hyperthermia therapy, and wastewater treatment. [1][2][3][4][5][6][7] It is possible to incorporate magnetic nanoparticles (MNPs) into a nanofibrous membrane in three different ways: (a) by utilizing pre-synthesized MNPs prior to electrospinning;…”
Section: Introductionmentioning
confidence: 99%